Radiographic anatomy and barium sulfate contrast study of the gastrointestinal tract of eastern box turtles (Terrapene carolina carolina). Issue 5 (25th July 2019) - Houck, Emma L.; Cohen, Eli B.; Womble, Mandy; Lewbart, Gregory A.; Petritz, Olivia A.
Abstract: Gastrointestinal disorders are an important cause of morbidity in box turtles ( Terrapene carolina Carolina ), however published information is currently lacking on the normal radiographic anatomy, transit, and emptying times of the gastrointestinal tract. A total of 15 healthy box turtles were recruited for this prospective, anatomic, reference interval study. Three‐view radiographic series (vertical beam dorsoventral, horizontal beam latero‐lateral, and horizontal beam rostrocaudal views) were acquired prior to contrast administration, and following contrast administration at 0, 20, 40, 60, and 90 min, 2, 4, 8, 12, and 24 h post administration, and every 24 h thereafter until all contrast was eliminated (15 mL/kg barium sulfate diluted to 30% weight per volume was administered via orogastric gavage). Vertical beam dorsoventral and horizontal beam latero‐lateral views were of excellent quality to identify gastrointestinal structures. The horizontal beam rostrocaudal view immediately postcontrast administration provided gastric and pyloric identification but had lesser diagnostic use at later time points due to anatomical superimposition. The gastrointestinal tract was composed of a tubular stomach, a pyloric sphincter near midline, a duodenum with a cranial flexure in the right cranial coelomic cavity, small intestines within the right coelom, a small cecal bulb, and a transverse and descending colon. Contrast media entered the large intestine by 24 h in all turtles, and a pyloro‐colic indentation was noted at the proximal descending colon. The large intestinal emptying was highly variable due to the interindividual variability of contrast sequestration within the cecal bulb. Findings from the current study serve as a reference on the gastrointestinal anatomy, transit, and emptying times in healthy eastern box turtles; and introduce a novel, horizontal beam, rostrocaudal view for gastrointestinal contrast studies in chelonians.